Repeat length variations in polyglutamine disease-associated genes affect body mass index - Gardiner, Sarah L; de Mutsert, Renée; Trompet, Stella; Boogaard, Merel W; van Dijk, Ko Willems; Jukema, P J Wouter; Slagboom, P Eline; Roos, Raymund A C; Pijl, Hanno; Rosendaal, Frits R; Aziz, N Ahmad (International Journal of Obesity, 2019)
The worldwide prevalence of obesity, a major risk factor for numerous debilitating chronic disorders, is increasing rapidly. Although a substantial amount of the variation in body mass index (BMI) is estimated to be heritable, the largest meta-analysis of genome-wide association studies (GWAS) to date explained only ~2.7% of the variation. To tackle this 'missing heritability' problem of obesity, here we focused on the contribution of DNA repeat length polymorphisms which are not detectable by GWAS. We determined the cytosine-adenine-guanine (CAG) repeat length in the nine known polyglutamine disease-associated genes (ATXN1, ATXN2, ATXN3, CACNA1A, ATXN7, TBP, HTT, ATN1 and AR) in two large cohorts consisting of 12,457 individuals and analyzed their association with BMI, using generalized linear mixed-effect models. We found a significant association between BMI and the length of CAG repeats in seven polyglutamine disease-associated genes (including ATXN1, ATXN2, ATXN3, CACNA1A, ATXN7, TBP and AR). Importantly, these repeat variations could account for 0.75% of the total BMI variation. Our findings incriminate repeat polymorphisms as an important novel class of genetic risk factors of obesity and highlight the role of the brain in its pathophysiology.